1998
DOI: 10.1007/s004280050254
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of hormone receptor and hormone-regulated protein expression in phyllodes tumour: comparison with fibroadenoma

Abstract: The histogenesis of phyllodes tumour (PT) and that of fibroadenoma (FA) of the breast appear to be closely related. FA is thought to be hormonally responsive, while the hormone-responsiveness of PT is uncertain. To gain insight into hormone-responsiveness of PT, we performed immunohistochemical analysis of oestrogen-regulated pS2 and androgen-regulated prostate-specific antigen (PSA) protein expression and also of oestrogen receptor (ER), progesterone receptor (PgR) and androgen receptor (AR) expression in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…Progesterone receptor expression is common, and estrogen a receptor expression is less common [25]. Estrogen a and progesterone receptor expression has been shown in 43% and 84%, respectively, of the epithelium and less than 5% of the stromal cells [26].…”
Section: Hormonal Receptorsmentioning
confidence: 98%
“…Progesterone receptor expression is common, and estrogen a receptor expression is less common [25]. Estrogen a and progesterone receptor expression has been shown in 43% and 84%, respectively, of the epithelium and less than 5% of the stromal cells [26].…”
Section: Hormonal Receptorsmentioning
confidence: 98%
“…6 The classical mediator of the response to estradiol and tamoxifen is the estrogen receptor (ER)-a, but in fibroadenomas and phyllodes tumors, ER-a is mainly expressed by epithelial cells, while its expression by stromal cells is controversial. [7][8][9][10] A recent study demonstrated that only the ER-b isoforms are found in stromal cells of the adult human mammary gland. 11 All these data taken together motivated us to investigate whether ER-b could be expressed by the stromal cells in fibroadenomas and phyllodes tumors.…”
mentioning
confidence: 99%
“…The PS2 expression in breast cancer relates to the expression of the estrogen receptor. The tumorsly negative for ER-dependent estrogen hardly express the PS2 [3] . The method of immunohistochemistry had testified that positive ER cells are not distributed on average in a body, every patient have two clone cells: ER positive or ER negative; We also know that the protein of ER may have faults, although it can combine with special hormones, it can't exert its functions so that hormones can't work properly.…”
Section: Discussionmentioning
confidence: 98%